The Sharia Economic Discourse in Social Media: Analysis of Public Discussion and Perception - Eti Jumiati (Islam Realitas: Journal of Islamic and Social Studies, 2025)
This study addresses the urgent need to understand how Islamic economics is discussed and perceived in the digital age, where social media has become a primary arena for shaping public opinion and financial literacy. Unlike earlier works that relied more on surveys or descriptive methods, this research utilizes Critical Discourse Analysis (CDA) to examine online conversations about zakat, waqf, and Islamic finance, and how ideology and power are reflected in these discourses. The findings reveal that Islamic economics has significant potential for growth through digital innovation, but faces challenges in financial literacy and product innovation. Theoretically, this study expands the application of CDA in Islamic economic discourse and provides practical contributions by offering insights into strengthening financial literacy, enhancing public education, and fostering innovation in Islamic financial products to ensure competitiveness in the digital economy. Therefore, it is crucial for all stakeholders to collaborate in improving public understanding and supporting the development of Islamic economics in Indonesia.